2004
DOI: 10.1007/s10653-004-1308-0
|View full text |Cite
|
Sign up to set email alerts
|

Principal Biogeochemical Factors Affecting the Speciation And Transport of Mercury through the terrestrial environment

Abstract: It is increasingly becoming known that mercury transport and speciation in the terrestrial environment play major roles in methyl-mercury bioaccumulation potential in surface water. This review discusses the principal biogeochemical reactions affecting the transport and speciation of mercury in the terrestrial watershed. The issues presented are mercury-ligand formation, mercury adsorption/desorption, and elemental mercury reduction and volatilization. In terrestrial environments, OH-, Cl- and S- ions have the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
143
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(150 citation statements)
references
References 100 publications
3
143
1
3
Order By: Relevance
“…The relationships, however, were weak and caused by the Truckee sites with higher silt and clay contents also showing higher Hg concentrations as compared to the sandier Little Valley sites. The lack of correlation of Hg content with clay content within individual sites, however, was surprising since a recent review (Gabriel and Williamson 2004) about Hg in soils and terrestrial environment suggested that clay minerals -along with a series of oxides and metal hydroxides -play an important role as sorbent for Hg in soils. However, differences in soil texture between the Truckee and Little Valley sites may co-determine differences in retention of C, N, and Hg at the sites.…”
Section: Soil Hg Concentrations and Relationship To Soil C And Nmentioning
confidence: 99%
“…The relationships, however, were weak and caused by the Truckee sites with higher silt and clay contents also showing higher Hg concentrations as compared to the sandier Little Valley sites. The lack of correlation of Hg content with clay content within individual sites, however, was surprising since a recent review (Gabriel and Williamson 2004) about Hg in soils and terrestrial environment suggested that clay minerals -along with a series of oxides and metal hydroxides -play an important role as sorbent for Hg in soils. However, differences in soil texture between the Truckee and Little Valley sites may co-determine differences in retention of C, N, and Hg at the sites.…”
Section: Soil Hg Concentrations and Relationship To Soil C And Nmentioning
confidence: 99%
“…Several abiotic and biotic factors contribute to the conversion of Hg species in soil. Soil organic matter, in particular dissolved organic matter, has been demonstrated to mediate the nonbiological process and affect Hg speciation (Schlüter 2000), while soil microbe is considered to play a key role in the biological process of Hg reduction and methylation in soil (Gabriel and Williamson 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments show that Fe(II) in minerals also can reduce Hg(II) to Hg(0). For example, in sealed, dark bottles, magnetite was found to reduce Hg(II) to Hg(0) within minutes (Wiatrowski et (Gabriel & Williamson, 2004). Although metals typically bind to acid sites (carboxyls, phenols, ammonium, alcohols, and thiols) in organic matter, Hg(II) binds preferentially with thiols and other reduced sulfur groups with which it forms strong covalent-like bonds.…”
Section: Oxidation-reduction and Sorption Reactionsmentioning
confidence: 99%